Voltammetric behavior of 4-acetamidohippuric acid and 4-acetamidobenzoic acid on a disposable carbon electrode and their determination in human urine - Wang, Lai-Hao; Zeng, Shih-Ying (Collection of Czechoslovak Chemical Communications, 2009)
The voltammetric behavior of 4-aminobenzoic acid (PABA) and its acetylated metabolite on glassy carbon, carbon fiber or carbon paste electrodes was investigated in an aqueous supporting electrolyte. 4-Aminohippuric acid (4-AHA), 4-acetamidobenzoic acid (4-AMB) and 4-acetamidohippuric acid (4-Ac-AHA) can be separated on a capillary carbon paste electrode in 0.1 M lithium perchlorate. The oxidation potentials of PABA, 4-AHA, 4-AMB and 4-Ac-AHA were 0.70, 0.88, 1.06 and 1.10 V on capillary CPE, respectively. The electrooxidation process is used for simultaneous quantitative determination of acetylated metabolites in urine.
Keywords: Aminohippuric Acids; kyseliny aminohippurové; elektrody; Financing, Organized; 4-Aminobenzoic Acid; kyselina 4-aminobenzoová; Urinalysis; analýza moči; Electrodes; elektrochemie; Electrochemistry; financování organizované